Savings And Loan Information System At KSU Madu Kencana Using AHP-WP Method - Ariyanto, Pradana Feri; Rianto; Wibawa (APPLIED SCIENCE AND TECHNOLOGY REASERCH JOURNAL, 2024)
Information technology has become a major driver of significant global development, changing the way we work, communicate, and access information. Koperasi Serba Usaha (KSU) Madu Kencana is a community-based financial institution with a savings and loan system that requires an information system that can support its operations to be faster, more precise, accurate, and relevant in improving the quality of service to customers and employee performance. The lag in the information system at KSU Madu Kencana will slow down service and data processing. The AHP method is used to determine the weight, then the WP method is used to determine the best alternative or priority order of alternatives. The results of this study are a savings and loan information system that can be used by KSU Madu Kencana in assessing loan applicants.